Effect of the size and distribution of supported Ru nanoparticles on their activity in ammonia synthesis under mild reaction conditions - Fernández, Camila; Sassoye, Capucine; Debecker, Damien P.; Sanchez, Clément; Ruiz, Patricio (Applied catalysis. A, General, 2014)
•A larger size of Ru nanoparticles leads to a higher (TOF).•Heterogeneous distribution of the size of Ru nanoparticles favors higher TOF.•Homogeneous distribution of size of Ru nanoparticles leads to lower TOF. Ru/γ-Al2O3 catalysts were prepared using three different methods: wet impregnation, colloidal method and microemulsion. Ru-supported nanoparticles with different average sizes and distribution of sizes were obtained. The catalysts were tested in ammonia synthesis under mild reaction conditions, namely low temperature (100°C) and low pressure (4bar), and characterized by N2 adsorption, XRD, XPS, TEM and TPR techniques. The results indicate that a good catalytic performance can be achieved by Ru supported nanoparticles fulfilling two requirements: (i) a relatively high average size (despite the usual assertion that only small particles are required) and (ii) a broad distribution of sizes that ensures the presence of both small particles, containing highly active sites, and large nanoparticles, which are shown to promote the reaction on small particles. This promotion results from a cooperative effect between small and large nanoparticles in good contact, which also allows keeping a highly reduced surface of ruthenium. It is proposed that, under mild reaction conditions, large Ru nanoparticles promote the ammonia synthesis reaction by allowing a more effective activation and transfer of hydrogen atoms, able to hydrogenate strongly adsorbed nitrogen atoms, and thus to release active sites for the activation of N2.